Follow-up procedures for non-muscle-invasive bladder cancer: an update. Issue 9 (September 2012) - Anastasiadis, Anastasios; Cordeiro, Ernesto; Bus, Mieke TJ; Alivizatos, Gerasimos; de la Rosette, Jean JMCH; de Reijke, Theo M
Bladder carcinoma is the most common malignancy of the urinary tract. Approximately 75–85% of patients present with a disease that is confined to the mucosa (stage Ta, carcinoma in situ ) or submucosa (stage T1). The stratification of patients to low-, intermediate- and high-risk groups represents the cornerstone for the indication of adjuvant and follow-up treatment. Owing to the high recurrence rate of bladder tumors, a surveillance protocol is recommended to all patients. Currently, the combination of cystoscopy, imaging and urinary cytology represent the follow-up. A systematic review of the recent English literature on follow-up procedures of non-muscle-invasive bladder cancer is performed. The authors review the existing follow-up procedures, with a focus on novel molecular-targeted approaches. At the present time, the additional use and utility of urine-based molecular markers in the follow-up of patients remains unclear and we have to rely on cystoscopic evaluation adapted to risk group classification.